Aplikasi Pengolahan Data Mahasiswa pada AMIK Bina Sriwijaya Palembang menggunakan Microsoft Visual Basic.: Aplikasi Pengolahan Data Mahasiswa pada AMIK Bina Sriwijaya Palembang menggunakan Microsoft Visual Basic. - Akhmad Sayuti; Tri Suci Yulianti (Kilau Publishing, 2024)
The student data processing application at AMIK Bina Sriwijaya Palembang is designed to increase efficiency and accuracy in managing academic information. This application was developed using Microsoft Visual Basic, which provides an intuitive and easy-to-use graphical user interface. This system includes various features for managing student data and reporting. Currently, archival or bookkeeping student data processing still uses manual methods. Therefore, we need a student data processing system that can collect data and manage data so that it can be done quickly, efficiently and accurately. Creating a student data reporting system is carried out by collecting data, analyzing data, designing the system, and implementing the system. With this application, it is hoped that student data processing will be more efficient and can be monitored easily by lecturers and by the center. Using Microsoft Visual Basic as a development platform provides several benefits, including easy integration with Microsoft Access databases, ease of use for developers, and the ability to produce responsive desktop applications. The implementation results show that this application is able to reduce the time required for the administration process. With this system, it is hoped that the academic administration process at AMIK Bina Sriwijaya Palembang will become more efficient, accurate and well organized, so that it can support institutional goals in providing quality educational services.